2020
DOI: 10.1016/j.drugalcdep.2020.108176
|View full text |Cite
|
Sign up to set email alerts
|

Signal of increased opioid overdose during COVID-19 from emergency medical services data

Abstract: Highlights COVID-19 pandemic disrupted treatment service delivery and harm reduction. Individuals with opioid use disorder may be at heightened risk of opioid overdose. Emergency medical services (EMS) data is a timely source for overdose surveillance. Kentucky EMS opioid overdose runs increased significantly during COVID-19 period. In contrast, average EMS daily runs for other conditions leveled or declined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
370
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 365 publications
(388 citation statements)
references
References 10 publications
16
370
2
Order By: Relevance
“…We used data from the EMS electronic medical records and the coroner's office to measure changes in the rates of overdose CFS and deaths after implementation of the COVID-19 stay-at-home order. The increases we observed-CFS in which naloxone was administered and overdose deaths-are consistent with recent studies [16,22]. Looking at several micro datasets in the same jurisdiction, our study additionally revealed that increases in overdoses were consistent across age and racial/ethnic groups, as well as spatially in high-volume zip codes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We used data from the EMS electronic medical records and the coroner's office to measure changes in the rates of overdose CFS and deaths after implementation of the COVID-19 stay-at-home order. The increases we observed-CFS in which naloxone was administered and overdose deaths-are consistent with recent studies [16,22]. Looking at several micro datasets in the same jurisdiction, our study additionally revealed that increases in overdoses were consistent across age and racial/ethnic groups, as well as spatially in high-volume zip codes.…”
Section: Discussionsupporting
confidence: 91%
“…Some evidence suggests that spikes have occurred in opioid overdoses in several jurisdictions across the U.S. during the COVID-19 pandemic [9][10][11][12][13][14][15][16][17][18]. To date, no national data exist to assess the impact to overdose events of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The results of our study are interesting to compare with a study from Kentucky, a state which has also been greatly affected by substance use disorder, demonstrating a 17% increase in the number of EMS opioid-related calls after a statewide COVID-19 emergency declaration (16).…”
Section: Accepted Manuscriptmentioning
confidence: 61%
“…The COVID-19 pandemic is likely to be considered a traumatic event, especially by those whose life circumstances have been affected. The pandemic has also presented particular challenges for individuals who struggle with substance use due to the fact that social isolation and despair are risk factors for the development and exacerbation of addiction (11,12). Professionals across multiple disciplines have raised alarms about the potential for increased family violence or intimate partner violence [e.g.…”
Section: Introductionmentioning
confidence: 99%